2010
DOI: 10.1016/s1130-1473(10)70063-4
|View full text |Cite
|
Sign up to set email alerts
|

Early mortality in spontaneous supratentorial intracerebral haemorrhage

Abstract: SummaryBackground. Spontaneous supratentorial intracerebral haemorrhage is a severe, frequent, and poorly understood condition. Despite the publication of 12 randomised controlled trials on this subject, the role of surgery remains controversial and no treatment has proved to be effective. We report on a ten year prospective cohort study based on a defined population treated with or without surgery and their outcome in terms of early survival.Methods. Population based, ten year prospective observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…Reichart R et al stated that patients suffering from medium-sized lobar hemorrhage should undergo surgery, especially if GCS was less than 7 [20]. In STICH II trial the fatality at 6 months follow-up was 18% in the early surgery group when set side by side with 24% observed in early conservative group and deduced that early surgery in patients with superficial spontaneous ICH had better chance of survival [21,22]. The STICH Trial done in 2005 showed that 26% of the patients randomised to early surgery had a better prognosis compared with 24% of the patients randomised to initial conservative treatment having a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Reichart R et al stated that patients suffering from medium-sized lobar hemorrhage should undergo surgery, especially if GCS was less than 7 [20]. In STICH II trial the fatality at 6 months follow-up was 18% in the early surgery group when set side by side with 24% observed in early conservative group and deduced that early surgery in patients with superficial spontaneous ICH had better chance of survival [21,22]. The STICH Trial done in 2005 showed that 26% of the patients randomised to early surgery had a better prognosis compared with 24% of the patients randomised to initial conservative treatment having a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were comparable to those in earlier studies. [6][7][8]13,16 Hematoma puncture and aspiration were initially applied when treating ICH patients in whom the hematoma volume was 40 ml or less. 18 Studies have proven that up to 80% of the hematoma would become a dense clot within a few hours after ictus, 9 and minimally invasive aspiration with subsequent fibrinolytic therapy requires days to evacuate a dense clot.…”
Section: Discussionmentioning
confidence: 99%
“…65 ( 55-74) en recientes publicaciones siendo el principal factor asociado y desencadenante de la HIE 6,7 . Lo encontrado en este estudio no es divergente a los resultados mostrados por lo diferentes estudios latinoamericanos, norteamericanos y europeos, se encontró una mortalidad del 12% durante toda la estancia hospitala-ria muy cercana a lo referenciado por Samphron et al 16 , encontramos que hipertensión arterial y la localización de los sangrados, fue diferente, se encontró como antecedentes único la HTA en un 38% y sumada a otras patologías un 7% y sin referir ningún antecedente hasta el 40% de esta población. Se propone realizar estudios que determi-nen si una deficiente información a los acompañantes y a los pacientes en la prevención primaria secundaria de la HTA es determinante en el desarrollo posterior de HIE y se espera que la hipertensión arterial sea descrita como antecedente principal único o acompañado de otros.…”
Section: Características Clínicas Y Paraclínicas Edad Mediana (Riq)unclassified